Strategi Digital Marketing Livin’ By Mandiri dalam Meningkatkan Nasabah (Bank Mandiri Yogyakarta) - Imas Rizki Amalia Kinanthi; Uswatun Chasanah (Syntax Idea, 2012)
Bank Mandiri Yogyakarta faces challenges in expanding its customer base and increasing the loyalty of existing customers. Therefore, Bank Mandiri Yogyakarta decided to use a digital marketing strategy to reach more customers and strengthen relationships with existing customers. to provide an understanding of the Livin' by Mandiri digital marketing strategy and how this strategy can help Bank Mandiri Yogyakarta increase the number of customers and strengthen relationships with existing customers. The results of this research provide information about various ways to market products or brands through digital information technology and provide solutions to overcome the obstacles faced by Bank Mandiri Yogyakarta in the process of implementing digital marketing. The research method used in this PDF is a qualitative research method. The data collection technique used in this research is interviews with several parties, namely Bank Mandiri Yogyakarta employees who have an understanding of digital marketing, namely customer service officers (CSO) and customer service representatives (CSR), as well as documentation in the form of archives obtained through literature and websites. related to Bank Mandiri's marketing strategy. In this research, triangulation was carried out by combining primary data and secondary data obtained through interviews and literature study. The implication of this research is that the banking industry in Indonesia can utilize the Livin' by Mandiri digital marketing strategy as an example to develop a more effective and efficient marketing strategy. Apart from that, this research can also help the banking industry in Indonesia to understand more deeply the importance of using digital information technology in marketing products or brands.